Tropical anurans mature early and die young: Evidence from eight Afromontane Hyperolius species and a meta-analysis. - Ulrich Sinsch; Jonas Maximilian Dehling (PLoS ONE)
Age- and size-related life-history traits of anuran amphibians are thought to vary systematically with latitude and altitude. Because the available data base is strongly biased towards temperate-zone species, we provide new estimates on eight afrotropical Reed Frog species. A meta-analysis of the demographic traits in 44 tropical anuran species aims to test for the predicted clinal variation and to contrast results with variation detected in temperate-zone species. The small-sized reed frogs reach sexual maturity during the first or second year of life, but longevity does not exceed three to four years. Latitudinal effects on demographic life-history traits are not detectable in tropical anurans, and altitudinal effects are limited to a slight size reduction at higher elevations. Common features of anuran life-history in the tropics are early sexual maturation at small size and low longevity resulting in low lifetime fecundity. This pattern contrasts with that found in temperate-zone anurans which mature later at larger size and grow considerably older yielding greater lifetime fecundity than in the tropics. Latitudinal and altitudinal contraction of the yearly activity period shape the evolution of life-history traits in the temperate region, while trait variation in the tropics seems to be driven by distinct, not yet identified selective forces.